Hubungan Fakta Dan Makna Pada Prinsip Verifikasi Perspektif Alfred Jules Ayer - Mu’minatus Fitriati Firdaus (Arete, 2017)
This study discusses the relationship between meaning and fact in principle of verification on science. This research is a library research that uses linguistic analysis method to make the research become clear, biodegradable and explicit. The aim of this study is to explain systematically the relationship of meaning and fact based on Alfred Jules Ayer’s theory that is through the principle of verification with several propositions, the reader can clearly understand that any meaningful proposition may not be verifiable at all and the principle of verification cannot be applied fully to the social sciences and theology.